Effect of different curing method for coconut shell concrete - Vijendran, Morogan (2017)
A study on flexural strength of Coconut Shell Concrete(CSC) by different type of curing method. The concrete produced by using 25% of coconut shell in coarse aggregates satisfies the minimum necessities of concrete. CSC has superior workability because of the smooth surface on one side of the shells. The impact resistance of CSC is high when compared with conventional concrete. Curing is the maintaining of a satisfactory moisture content and temperature in concrete during its early stage so that desired properties may develop. The strength and durability of concrete will be fully achieved if the concrete sample pass through the curing process. This study is focused on flexural strength of CSC which varies by different type of curing method. Two types of concrete mix were chosen for this study which is CSC and Normal Concrete(NC). The mixture of concrete poured in 24 mould as simple beam and pass through two type curing methods for 7 days and 28 days. Flexural tests were carried out to determine the flexural strength using simple beam specimens. It was observed that when CSC pass through two types of curing method, flexural strengths are comparable in between two curing methods. It was observed that when coconut shells as aggregate in proportions of 25% was used in CSC, flexural strengths comparable to that of NC can be obtained.